Transgenic minipig model of Huntington's disease exhibiting gradually progressing neurodegeneration - Taras Ardan; Monika Baxa; Božena Levinská; Miroslava Sedláčková; The Duong Nguyen; Jiří Klíma; Štefan Juhás; Jana Juhásová; Petra Šmatlíková; Petra Vochozková; Jan Motlík; Zdenka Ellederová (The Company of Biologists, 2020)
Recently developed therapeutic approaches for the treatment of Huntington's disease (HD) require preclinical testing in large animal models. The minipig is a suitable experimental animal because of its large gyrencephalic brain, body weight of 70-100 kg, long lifespan, and anatomical, physiological and metabolic resemblance to humans. The Libechov transgenic minipig model for HD (TgHD) has proven useful for proof of concept of developing new therapies. However, to evaluate the efficacy of different therapies on disease progression, a broader phenotypic characterization of the TgHD minipig is needed. In this study, we analyzed the brain tissues of TgHD minipigs at the age of 48 and 60-70 months, and compared them to wild-type animals. We were able to demonstrate not only an accumulation of different forms of mutant huntingtin (mHTT) in TgHD brain, but also pathological changes associated with cellular damage caused by mHTT. At 48 months, we detected pathological changes that included the demyelination of brain white matter, loss of function of striatal neurons in the putamen and activation of microglia. At 60-70 months, we found a clear marker of neurodegeneration: significant cell loss detected in the caudate nucleus, putamen and cortex. This was accompanied by clusters of structures accumulating in the neurites of some neurons, a sign of their degeneration that is also seen in Alzheimer's disease, and a significant activation of astrocytes. In summary, our data demonstrate age-dependent neuropathology with later onset of neurodegeneration in TgHD minipigs.